Racial disparities in characteristics and outcomes of patients undergoing mitral transcatheter edge-to-edge repair - Shechter, Alon; Kaewkes, Danon; Makar, Moody; Patel, Vivek; Koren, Ofir; Koseki, Keita; Solanki, Aum; Dhillon, Manvir; Nagasaka, Takashi; Skaf, Sabah; Chakravarty, Tarun; Makkar, Raj R.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background There are scarce data regarding the post-mitral transcatheter edge-to-edger repair (TEER) course in different racial groups. Objective To assess the impact of race on outcomes following TEER for mitral regurgitation (MR). Methods This is a single-center, retrospective analysis of consecutive TEER procedures performed during 2013–2020. The primary outcome was the composite of all-cause mortality or heart failure (HF) hospitalizations along the first postprocedural year. Secondary outcomes included individual components of the primary outcome, New York Heart Association (NYHA) class, MR grade, and left ventricular mass index (LVMi). Results Out of 964 cases, 751 (77.9%), 88 (9.1%), 68 (7.1%), and 57 (5.9%) were whites, blacks, Asians, and Hispanics, respectively. At baseline, non-whites and blacks were younger and more likely be female, based in lower socioeconomic areas, not fully insured, diagnosed with functional MR, and affected by biventricular dysfunction. Intra-procedurally, more devices were implanted in blacks. At 1-year, non-whites (vs. whites) and blacks (vs. non-blacks or whites) experienced higher cumulative incidence of the primary outcome (32.9% vs. 22.5%, p = 0.002 and 38.6% vs. 23.4% or 22.5%, p = 0.002 or p = 0.001, respectively), which were accounted for by hospitalizations in the functional MR sub-cohort (n = 494). NYHA class improved less among blacks with functional MR. MR severity and LVMi equally regressed in all groups. White race (HR 0.62, 95% CI 0.39–0.99, p = 0.047) and black race (HR 2.07, 95% CI 1.28–3.35, p = 0.003) were independently associated with the primary outcome in functional MR patients only. Conclusion Mitral TEER patients of different racial backgrounds exhibit major differences in baseline characteristics. Among those with functional MR, non-whites and blacks also experience a less favorable 1-year clinical outcome.